La planificación financiera y su relación con el desarrollo de la gestión operativa de la empresa Af Boullosa EIRL, periodo 2023 - Gallardo Lachuma, Jose Esteban (2024)
Financial planning is a very important instrument for the growth of any company, since its use would guarantee compliance with the objectives established by management, as well as contribute to ensuring that operational management can be adequately developed for the benefit of the company. The research is titled "Financial planning and its relationship with the development of operational management of the company AF Boullosa EIRL, period 2023", the central objective is to determine the relationship between financial planning and financial management. The study corresponded to a quantitative model and descriptive correlational design, with the survey being the technique and the questionnaire as the data collection instrument, which for its application was validated through the reliability test (0.923) and applied in a sample of 35 individuals. From the evaluation and analysis of the information in the spss v25 statistical software, a moderate positive relationship was determined, supported by Pearson's Rho coefficient, which was 0.508 and the degree of significance was 0.002.